Anthraquinone-2-sulfonate immobilized to conductive polypyrrole hydrogel as a bioanode to enhance power production in microbial fuel cell. (November 2017) - Tang, Xinhua; Ng, How Yong
Highlights: Anthraquinone-2-sulfonate was covalently grafted on conductive polypyrrole hydrogel. CPH/AQS enhanced biofilm formation. CPH/AQS reduced charge transfer resistance. CPH/AQS increased power density in MFC. Abstract: In this study, anthraquinone-2-sulfonate (AQS), a redox mediator, was covalently bound to conductive polypyrrole hydrogel (CPH) via electrochemical reduction of the in-situ -generated AQS diazonium salts. The porous structure and hydrophilic surface of this CPH/AQS anode enhanced biofilm formation while the AQS bound on the CPH/AQS anode worked as a redox mediator. The CPH/AQS bioanode reduced the charge transfer resistance from 28.3 Ω to 4.1 Ω while increased the maximum power density from 762 ± 37 mW/m 2 to 1919 ± 69 mW/m 2, compared with the bare anode. These results demonstrated that the facile synthesis of the CPH/AQS anode provided an efficient route to enhance the power production of microbial fuel cell (MFC).